Fire Risk Assessment in Hotels and Resorts Using FRAME (A case study of four-star hotels in Mashhad) - Meysam REZAEE; Saeed GIVEHCHI; Mahnaz NASRABADI (Shahid Sadoughi University of Medical Sciences, 2017)
Introduction: Fire has devastating fatal, financial, and environmental consequences for the community, and there are many victims annually in different societies. With an estimated population of about three million, Mashhad is a religious metropolis in Iran, which is yearly visited by a large number of tourists. Consequently, it is ranked as the first city in Iran regarding the number of accommodations and hotels. Methods: The present study aimed to evaluate fire risk in some four-star hotels using Fire Risk Assessment Method (FRAME). Fire Risk Assessment Method is the most comprehensive, transparent, and practical calculation method for evaluating fire risk in the buildings that can be used to separately assess fire risk for the building, its content, occupants, and activities in it. In this method, at first the building was divided into different compartments and for each a separate spreadsheet/information checklist was completed. Then, the FRAME spreadsheet was filled using Excel and finally the result of risk assessment was separately calculated by the software. Results: The results of the evaluation revealed that the highest risk level in Mashhad’s hotel belongs to the estimated risk for occupants. Regarding the fire occurrence, the most important and the riskiest compartment/part of the investigated hotels were the basements where installations units, warehouses, and laundries are located. Conclusion: By reviewing the results, the proposed solution to reduce the fire risk of four-star hotels in Mashhad was exact implementation of the national regulations and regulations of the Construction Engineering Organization and Fire department. Moreover, since fire risk is high in the basement levels, special supervisory actions should be performed to decrease fire risk in these sections.